Réponses

2014-04-02T10:35:21+02:00
Bonjour,

2:3(y-4)=5:4-7y

\dfrac{2}{3}(y-4)=\dfrac{5}{4}-7y\\\\\dfrac{2}{3}y-\dfrac{8}{3}=\dfrac{5}{4}-7y\\\\\dfrac{2}{3}y+7y=\dfrac{5}{4}+\dfrac{8}{3}\\\\\dfrac{2}{3}y+\dfrac{21}{3}y=\dfrac{15}{12}+\dfrac{32}{12}\\\\\dfrac{23}{3}y=\dfrac{47}{12}\\\\y=\dfrac{47}{12}\times\dfrac{3}{23}\\\\y=\dfrac{47}{4}\times\dfrac{1}{23}\\\\y=\dfrac{47}{92}

(y-2):4=(5:4)y-y

\dfrac{y-2}{4}=\dfrac{5}{4}y-y\\\\\dfrac{y-2}{4}=\dfrac{5}{4}y-\dfrac{4}{4}y\\\\\dfrac{y-2}{4}=\dfrac{5y-4y}{4}\\\\y-2=5y-4y\\\\y-5y+4y=2\\\\0y=2\\\\Equation\ \ impossible

(3:2)-(7y:4)=(5[2-y]:2)-1

\dfrac{3}{2}-\dfrac{7y}{4}=\dfrac{5(2-y)}{2}-1\\\\\dfrac{6}{4}-\dfrac{7y}{4}=\dfrac{10(2-y)}{4}-\dfrac{4}{4}\\\\\dfrac{6-7y}{4}=\dfrac{10(2-y)-4}{4}\\\\6-7y=10(2-y)-4\\\\6-7y=20-10y-4\\\\-7y+10y=20-4-6\\\\3y=10\\\\y=\dfrac{10}{3}